THE EFFECT OF CHATGPT ON STUDENTS’ LANGUAGE CHOICE IN WRITING RECOUNT TEXT AT SMP NEGERI 1 PEMATANGSIANTAR - Esra Delima Hutabarat; Selviana Napitupulu (Penelitian dan Pengembangan Ilmu, 2025)
Writing is a crucial English language acquisition skill that calls for precision, coherence, and acceptable language use. However, choosing appropriate language for recount writings is a challenge for many students. The purpose of this study was to investigate how ChatGPT affected the language choices made by eighth-grade students at SMP Negeri 1 Pematangsiantar when they were composing recount texts. A pre-experimental one-group pre-test and post-test design was used in this quantitative study. Purposive sampling was used to choose 24 students for the sample. Language choice in vocabulary, grammar, sentence structure, and mechanics was evaluated through a writing test. Descriptive statistics and a paired-sample t-test were used to assess the data. The results revealed a mean difference of 33.83 points, with the mean score rising from 52.92 in the pre-test to 86.75 in the post-test. After utilizing ChatGPT, the t-test result showed a statistically significant improvement. As a result, ChatGPT influences students' writing language choices in a good way.